2016
DOI: 10.1002/pssc.201510229
|View full text |Cite
|
Sign up to set email alerts
|

Gamma‐ray tolerance of CdS/CdTe photodiodes for radiation tolerant compact image sensor with field emitter array

Abstract: The effect of gamma irradiation on two types (superstrate‐ and substrate‐type) of CdS/CdTe photodiodes, which we have proposed as potential photoconducting films for compact image sensors with a field emitter array (FEA), was investigated. A 60Co gamma‐ray source was employed, and the total gamma irradiation dose was more than 500 kGy. For the superstrate‐type structure, the irradiation caused the short‐circuit current density (JSC) to decrease, probably due to the resulting decreased transmittance of the glas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 11 publications
(24 reference statements)
0
14
0
Order By: Relevance
“…The value of short current density (J SC ) decreased in the early stage of the dose. 22,23) After the first dose (75 kGy), the coloring of the glass substrate due to γ-ray absorption was observed. 22,23) We concluded that the decrease was due to the decrease in transmittance of the glass substrate.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The value of short current density (J SC ) decreased in the early stage of the dose. 22,23) After the first dose (75 kGy), the coloring of the glass substrate due to γ-ray absorption was observed. 22,23) We concluded that the decrease was due to the decrease in transmittance of the glass substrate.…”
Section: Resultsmentioning
confidence: 99%
“…22,23) After the first dose (75 kGy), the coloring of the glass substrate due to γ-ray absorption was observed. 22,23) We concluded that the decrease was due to the decrease in transmittance of the glass substrate. Furthermore, open circuit voltage (V OC ) slightly decreased.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 47 ] CdTe‐based thin‐film solar cells and photodiodes efficiently tolerate high gamma‐ray and proton exposures. [ 48–52 ]…”
Section: Radiation Resistant Functional Optoelectronic Materialsmentioning
confidence: 99%
“…In recent years, vacuum devices are also studied for photodetection due to the advantages of high-sensitivity and high resistance to radiation [ 25 ]. The main structure of vacuum photodetectors includes a photoconductor anode and a cold cathode field emitter array (FEA), which can be made into a large-area flat panel detector.…”
Section: Introductionmentioning
confidence: 99%